Ankle moment generation and maximum-effort curved sprinting performance - Luo, G.; Stefanyshyn, D. (Journal of Biomechanics, 2012)
Turning at high speed along acute curves is crucial for athletic performance. One determinant of curved sprinting speed is the ground reaction force that can be created by the supporting limb; the moment generated at the ankle joint may influence such force generation. Body lean associated with curved sprints positions the ankle joints in extreme in-/eversion, and may hinder the ankle moment generation. To examine the influence of ankle moment generation on curved sprinting performance, 17 male subjects performed maximum-effort curved sprints in footwear with and without a wedge. The wedged footwear was constructed with the intention to align the ankle joints closer to their neutral frontal-plane configuration during counter-clockwise curved sprints so greater joint moments might be generated. We found, with the wedged footwear, the average eversion angle of the inside leg ankle was reduced, and the plantarflexion moment generation increased significantly. Meanwhile, the knee extension moment remained unchanged. With the wedged footwear, stance-average centripetal ground reaction force increased significantly while no difference in the vertical ground reaction force was detected. The subjects created a greater centripetal ground reaction impulse in the wedged footwear despite a shortened stance phase when compared to the control. Stance-average curved sprinting speed improved by 4.3% with the wedged footwear. The changes in ankle moment and curved sprinting speed observed in the current study supports the notion that the moment generation at the ankle joint may be a performance constraint for curved sprinting.